Edukasi Kesehatan untuk Meningkatkan Pengetahuan Pasien dan Keluarga tentang Tuberkulosis Paru - Adja, Hesti; Suhita, Byba Melda; Suprataba, Suprataba (Yayasan Inspirasi El Burhani, 2026)
Introduction: Pulmonary Tuberculosis (TB) remains a major public health challenge in Indonesia. Limited knowledge among patients and families regarding TB transmission, prevention, and treatment adherence contributes to persistent cases, including those reported at Madani Regional General Hospital, Palu. Strengthening health education is essential to improve disease control efforts. Objective: This community service program aimed to enhance patients’ and families’ understanding of Pulmonary Tuberculosis, including its definition, clinical manifestations, modes of transmission, prevention strategies, appropriate treatment, and the consequences of non-adherence to therapy. Method: The activity was conducted in the Durian Ward of Madani Hospital through health education sessions using lectures, discussions, leaflet distribution, and demonstrations. Knowledge improvement was assessed using oral pre- and post-tests involving TB patients and their accompanying family members. Result: The program resulted in a substantial increase in participant knowledge. Pre-test findings revealed that only about 20% of participants could correctly answer basic questions about TB. Post-intervention, approximately 90% demonstrated accurate understanding of the presented material and were able to apply preventive practices, such as correct handwashing and mask usage. Participants expressed commitment to practicing prevention at home and during hospital visits. Conclusion: The community service intervention effectively improved patient and family knowledge regarding Pulmonary Tuberculosis. Continuous educational efforts by healthcare professionals are crucial to reinforcing treatment adherence and reducing transmission risk within healthcare and community settings.